Linking DSSAT V3 to a relational database: the AGROSYS–DSSAT interface - Pampulim Caldeira, Carlos; Aguiar Pinto, Pedro (Computers and electronics in agriculture, 1998)
This paper presents an information system that links the decision support system DSSAT V3 to a relational database named AGROSYS. They are coupled by a GUI (graphical user interface) which links crop simulation models in DSSAT and AGROSYS. This prototype runs on Microsoft Windows 95 with Access Version 7.0 or later. AGROSYS is a structured information system, which gives the user access to both data and information on many different agrobiological subjects. This information has been collected from literature reviews (including DSSAT manuals), field experimentation and the contributions of experts in many different areas. Since a relational database makes explicit and normalizes the system's dataset, the information is free of any redundancy or ambiguity, being easily updated.